A novel method of brazing Cu/Cu‐7.0Ni‐9.3Sn‐6.3P/Cu using microwave hybrid heating: Ein neuartiges Verfahren zum Hartlöten von Cu / Cu‐7, 0Ni‐9, 3Sn‐6, 3P / Cu mittels Mikrowellen‐Hybridheizung. Issue 3 (April 2017) - Maisarah, L.; Yusof, F.; Ramesh, S.; Ariga, T.; Hamdi, M.
Abstract: Bulk copper and Cu‐7.0Ni‐9.3Sn‐6.3P (in wt %) filler alloys were brazed by microwave hybrid heating (MHH) and the results were compared with brazing using conventional furnace heating. Characterizations of the brazed joint were investigated through field emission scanning electron microscope, X‐ray diffraction, shear strength test and Vicker's microhardness test. It was observed that microwave heating decreased to 94 % of total processing time compared to conventional heating. Metallurgical study showed the formation of the alpha‐copper, copper phosphide and nickel phosphide intermetallics at the joint interface for both heating methods. The reaction layer thickness of microwave brazed joint was three times thinner compared to the conventionally brazed joint. The optimum shear strength of the microwave brazed joints was found to be 108.8 MPa while it was 16 % higher for the samples brazed using the conventional method. The failures of the microwave brazed joints showed a brittle cleavage structure while a mixed cleavage structure with tearing regions was observed for the conventionally brazed joints.